The Determinant of Human Development in Eastern Part of Indonesia during 2012-2020 - Najwa Khairina; Arbi Wijaya (Signifikan: Jurnal Ilmu Ekonomi, 2023)
Improving human resource quality in Eastern Indonesia has become a primary concern in many development programs enacted in Indonesia. The KTI regions needed to catch up and often experienced development problems. Several challenges, such as the significant disparity in education and health facilities compared to the western part of Indonesia, have hindered the development process of KTI. This research aims to find the determinants of human development in KTI. We analyze the regional fiscal dependency ratio, employment level, allocation of DAU (general allocation fund) by the central government, and poverty gap level as determinants of the Human Development Index in KTI. Using the Fixed Effect panel data analysis, we found that the general allocation fund, employment, and fiscal dependency ratio are positively associated with HDI in KTI regions. In contrast, the poverty gap is negatively associated with HDI in KTI regions. Our empirical finding implies that central government transfers play an essential role in the human development process, while the poverty problem is one of the main obstacles to improving the human resources quality in KTI regions.JEL Classification: H80, L38, O15How to Cite:Khairina, N., & Wijaya, A. (2023). The Determinant of Human Development in the Eastern Part of Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 83-96. https://doi.org/10.15408/sjie.v12i1.29496.